Resistive Switching in Electrodeposited Prussian Blue Layers - Avila, Lindiomar Borges (Materials (Basel), 2020)
Prussian blue (PB) layers were electrodeposited for the fabrication of Au/PB/Ag stacks to study the resistive switching effect. The PB layers were characterized by different techniques to prove the homogeneity, composition, and structure. Electrical measurements confirmed the bipolar switching behavior with at least 3 orders of magnitude in current and the effect persisting for the 200 cycles tested. The low resistance state follows the ohmic conduction with an activation energy of 0.2 eV.